2017
DOI: 10.1556/168.2017.18.3.7
|View full text |Cite
|
Sign up to set email alerts
|

Phytophagous hoverflies (Diptera: Syrphidae) as indicators of changing landscapes

Abstract: Spatial and temporal differences in landscape patterns are of considerable interest for understanding ecological processes. In this study, we assessed habitat quality by using the Syrph The Net database and data on decreasing species richness over a 25-year period for the two largest phytophagous hoverfly genera (Merodon and Cheilosia). Furthermore, within this time frame, we explored congruence between ecological responses (species richness and Biodiversity Maintenance Function for these two genera) and lands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…Some studies have reported that abundance of some groups falls with habitat simplification 48 , while in other groups abundance increases 49 which was also recorded in our study. The sensitivity of many of these species to environmental conditions has led to several groups being recognised as bioindicators of conditions in agricultural systems, native ecosystem degradation and ecological restoration [50][51][52][53] . These studies, along with others in traditional silvopastoral systems 54 highlight the importance of promoting these systems for livestock farming allied with biodiversity conservation and conservation of ecosystem services, though care must be taken, since the effects can depend on the design of the system and tree species chosen 55 .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported that abundance of some groups falls with habitat simplification 48 , while in other groups abundance increases 49 which was also recorded in our study. The sensitivity of many of these species to environmental conditions has led to several groups being recognised as bioindicators of conditions in agricultural systems, native ecosystem degradation and ecological restoration [50][51][52][53] . These studies, along with others in traditional silvopastoral systems 54 highlight the importance of promoting these systems for livestock farming allied with biodiversity conservation and conservation of ecosystem services, though care must be taken, since the effects can depend on the design of the system and tree species chosen 55 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Jovičić et al (2017) showed that landscape structure and land use influence species compositions of two large phytophagous hoverflies genera (Merodon Meigen, 1803 and Cheilosia Meigen, 1822) differently in South-Eastern Europe [32]. Moreover, a study assessing the habitat quality in relation to decreased species richness of the same two genera in Serbia over a 25-year period [33] using CORINE land cover maps revealed that landscape structural changes, specifically in aggregation, isolation/connectivity, and landscape diversity, were significantly correlated with species richness loss. However, the UAV classified land cover map provides much greater precision and more details than CORINE (CLC), which greatly contribute to obtaining more accurate results and a more realistic picture of species richness in studied ecosystems.…”
Section: Potential and Recent Hoverfly Species Richness In Relation To Habitat Condition Assessmentmentioning
confidence: 99%
“…Regarding the pollinators referred to in this study, hoverflies are the most biologically diverse families of Diptera [28], and the most important pollinators besides bees [28][29][30]. As bioindicators of the ecosystem's condition [29], hoverflies serve as valuable model organisms in studies on both climate change and the change in landscape structure and land use [26][27][28][31][32][33]. Hoverflies occupy a wide variety of habitats, aside from extreme conditions, such as dry areas and frozen landscapes [29,30,34].…”
Section: Introduction 1general Overview and Objectives Of The Studymentioning
confidence: 99%
“…Species pools for each defined vegetation type were compiled separately based on expert opinion and information from the StN database. The database compiles information about distribution and habitat preferences for European hoverfly species and has been successfully used for habitat evaluations (Speight & Castella, 2001;Sommaggio & Burgio, 2014;Popov et al, 2017).…”
Section: Estimation Of Dark Diversitymentioning
confidence: 99%